The importance of independence from the government for the critical sting of the National Audit Office’s reports and their use of the Folketing - Triantafillou, Peter; Christiansen, Flemming Juul (Politica, 2025)
The audit reports of the Danish National Audit Office are essential for public and parliamentary control of the government and the state’s use of public funds. According to the academic literature, the oversight function of national audit offices depends on their subordination to parliament rather than to the government. However, there are very few empirical studies of this thesis. This study examines whether the transfer of the Danish National Audit Office in 1991 from the Ministry of Economic Affairs to the Folketing has contributed to making the audit reports more critical and to increasing the Folketing’s use of these reports to ask the government critical questions. The study suggests that the transfer has contributed to making the reports more critical. However, the transfer has not had any clear impact on the Folketing’s use of the reports.